Social Media Use as an Impulsive ‘Escape From Freedom’ - Phil Reed (Psychological Reports, 2023)
It has been suggested that avoiding choice represents an anxiety-avoidance strategy, which has not been investigated in the context of social media. To this end, the current study explored the relationship between social media dependency and a preference for ‘forced’ choice, along with its association with anxiety, intolerance of uncertainty, and experiential avoidance. The sample comprised 151 volunteer participants (18–32 years) who completed a psychometric test battery, including: the Bergen Social Media Addiction Scale; Spielberger Trait Anxiety Inventory; Intolerance of Uncertainty Scale; and Brief Experiential Avoidance Questionnaire. They also undertook a behavioural assessment based on a paradigm developed for pigeons, in which they selected either a situation with a free choice of alternatives, and one with a forced choice. Intolerance of uncertainty mediated the relationship between social media dependency and anxiety. In addition, those with lower social media dependency preferred being able to choose the contingency they worked on, while those with higher scores exhibited no such preference. This partly confirmed that social media dependency is associated with a reduced preference for freedom, but does not suggest social media dependency actively produced a preference for a lack of freedom. The speed of decision making was also faster in those with high social media dependency scores, in line with previous findings that they show higher levels of impulsive behaviours. The results suggest that anxiety and social media dependency are related, and fear of uncertainty and is linked with digital experiential avoidance.